Welfare Impact of Value-Added Tax Reform : The Case of the Democratic Republic of Congo - Adoho, Franck M. (World Bank, Washington, DC, 2019)
The adoption of the value-added tax the Democratic Republic of Congo in 2012 led to price increases that are thought to adversely affect the welfare of most Congolese households. To date, research has not yet examined the poverty and distributional impacts of this tax reform. Using data from the 2012 Living Standards Measurement Survey, this paper investigates whether the current value-added tax regime, with its exemptions, is progressive. Relying on the Quadratic Almost Ideal Demand System and several welfare measures, the analysis finds that the adoption of the value-added tax erodes the purchasing power of all Congolese households by a factor of 10 to 12 percent. Yet, the value-added tax appears to be highly progressive. Households in the top food expenditure quintile bears approximately 40 percent of the welfare loss compared with less than 10 percent among households in the bottom food expenditure quintile. Other inequality measures, such as the Gini coefficient, further support this finding that the value-added tax is progressive. Finally, the study finds that the adoption of the value-added tax leads to a worsening of the food poverty headcount by approximately 1.2 percentage points.